2015
DOI: 10.1007/s00198-015-3083-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum uric acid is associated with quantitative ultrasound parameters in men: data from the Camargo cohort

Abstract: Higher serum uric acid levels in men older than 50 years are positively associated with QUS parameters. These data might suggest a better bone quality in men with elevated serum uric acid values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In 2011, Nabipour et al12 first reported that high serum UA concentrations were associated with high BMD values at all sites, including LS, TH, FN and WB, in a population-based cohort of 1,705 older men (aged ≥70 years). A recent study on 868 men older than 50 years showed that the BMD at LS, FN and TH was significantly higher in men with higher serum UA levels 15. In Chinese males with diabetes mellitus (54.14±11.49 years), higher serum UA was positively associated with higher BMD at all sites 16.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In 2011, Nabipour et al12 first reported that high serum UA concentrations were associated with high BMD values at all sites, including LS, TH, FN and WB, in a population-based cohort of 1,705 older men (aged ≥70 years). A recent study on 868 men older than 50 years showed that the BMD at LS, FN and TH was significantly higher in men with higher serum UA levels 15. In Chinese males with diabetes mellitus (54.14±11.49 years), higher serum UA was positively associated with higher BMD at all sites 16.…”
Section: Discussionmentioning
confidence: 94%
“…Many studies12,15–17 noticed a protective effect of UA on BMD at all sites, or only at LS. In 2011, Nabipour et al12 first reported that high serum UA concentrations were associated with high BMD values at all sites, including LS, TH, FN and WB, in a population-based cohort of 1,705 older men (aged ≥70 years).…”
Section: Discussionmentioning
confidence: 99%
“…Among 32 studies, 21 28 29 30 31 32 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 and 11 23 24 25 26 27 60 61 62 63 64 65 considered VIT D and SUA as the outcome, respectively. Within the 21 studies with VIT D outcome, 6 31 32 44 48 49 50 provided data of SUA and VIT D levels as continuous variables, 14 28 29 30 31 32 45 46 47 49 52 53 54 57 59 assessed association between SUA level as continuous data and categorical VIT D status, while 3 55 56 58 provided categorical data for both.…”
Section: Resultsmentioning
confidence: 99%
“…Within the 21 studies with VIT D outcome, 6 31 32 44 48 49 50 provided data of SUA and VIT D levels as continuous variables, 14 28 29 30 31 32 45 46 47 49 52 53 54 57 59 assessed association between SUA level as continuous data and categorical VIT D status, while 3 55 56 58 provided categorical data for both. For the 11 studies with SUA outcome, 1 64 had continuous data for both VIT D and SUA levels, 9 23 24 25 27 60 61 62 63 65 provided continuous data for VIT D level and categorical SUA status, and 2 25 26 provided categorical data for both.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation